2018
DOI: 10.1155/2018/9253036
|View full text |Cite
|
Sign up to set email alerts
|

AIMP2-DX2 Promotes the Proliferation, Migration, and Invasion of Nasopharyngeal Carcinoma Cells

Abstract: Nasopharyngeal carcinoma (NPC) is a head and neck tumor with high degree of malignancy and with high incidence especially in southern China. AIMP2-DX2, one isoform of the aminoacyl-tRNA synthetase interacting multifunctional proteins (AIMPs), is shown to be a potential target in many cancers. However, the detailed mechanisms of AIMP2-DX2 in NPC development remain to be elucidated. Here, we found that the mRNA expression level of AIMP2-DX2 was significantly increased in NPC specimens, compared with normal nasop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…41,42 Previous studies showed that AIMP2 might serve as an important molecule in regulating cell proliferation and apoptosis after DNA damage through interacting with p53. 41,43 Moreover, AIMP2-DX2, one of variant splicing isoform of AIMP, was significantly associated with the tumorigenesis, cancer cell proliferation, invasion, and migration in many cancers, including lung cancer, ovarian cancer, and nasopharyngeal carcinoma [44][45][46][47] In the study of Yin K et al, elevating the expression of AIMP2 splicing variation could shorten the survival of patients with tongue squamous cell carcinoma, which was also in high accordance with our study. 48 Taken together, AIMP2 may also serve as a novel therapeutic target of SKCM.…”
Section: Discussionsupporting
confidence: 89%
“…41,42 Previous studies showed that AIMP2 might serve as an important molecule in regulating cell proliferation and apoptosis after DNA damage through interacting with p53. 41,43 Moreover, AIMP2-DX2, one of variant splicing isoform of AIMP, was significantly associated with the tumorigenesis, cancer cell proliferation, invasion, and migration in many cancers, including lung cancer, ovarian cancer, and nasopharyngeal carcinoma [44][45][46][47] In the study of Yin K et al, elevating the expression of AIMP2 splicing variation could shorten the survival of patients with tongue squamous cell carcinoma, which was also in high accordance with our study. 48 Taken together, AIMP2 may also serve as a novel therapeutic target of SKCM.…”
Section: Discussionsupporting
confidence: 89%
“…However, a splice variant of AIMP2 lacking the second exon, AIMP2-DX2 (DX2), is overexpressed in many types of cancer. DX2 counteracts the anti-cancer activities of the full-length AIMP2 protein by competing with the normal binding partners of AIMP2 [ 47 , 48 , 49 ]. The same studies that showed how DX2 disrupts the normal function of AIMP2 also demonstrated clear overexpression of DX2 in lung, ovarian, and nasopharyngeal cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This competing function of DX2 against AIMP2 leads to the inhibition of the tumor suppressive roles of AIMP2 (Figure ). , In malignant lung cancers and chemoresistant ovarian cancers, the expression ratio of AIMP2-DX2 and AIMP2 is known to indicate a positive relationship with tumor progression. ,, Thus, inhibition of AIMP2-DX2 has attracted much attention as a promising therapeutic strategy for the treatment of prostate, nasopharyngeal, ovarian, and especially lung cancers. ,,,− Previous attempts at discovering the AIMP2-DX2 inhibitors from the chemical libraries were not successful. Only a few small molecule DX2 inhibitors, including SLCB050 (Figure ), were identified.…”
Section: Introductionmentioning
confidence: 99%